Effect of quenching medium on sliding tribology of self-lubricating Al-Cu metal matrix composites - Kumar P.; Srivastava V.K. (My University, 2025)
The cooling rate during fabrication affects the microstructural features and interface strength in metal matrix composites (MMCs). Thus, the present investigation is focused on characterizing the effect of quenching medium on wear and friction response of self-lubricating Al-Cu dual matrix composites. Mica was reinforced in Al-Cu metal matrix composites with the variation of weight percentage as 1%, 2%, 3%, 5%, 8% and 10%. A standard powder metallurgy route was adopted for fabrication. The sintered composites were normalized, and quenched in water, and oil. A pin on disc study was carried to investigate the friction and wear behavior of normalized, oil quenched, water quenched and as-prepared (green) composites. The results revealed that oil quenched composites exhibited the lowest friction coefficient and highest wear loss. The highest friction coefficient of ~0.8 was observed for normalized composites, whereas the highest friction coefficient for water quenched composites was ~0.6. The oil quenched composites exhibited about 8 ~ 15 times higher wear loss as compared to normalized and water quenched composites. Worn surfaces were analyzed under a scanning electron microscope to know the dominant wear mechanisms. The developed composites find potential applications in automotive industry such as pistons for petrol and diesel engines. Copyright © 2020 Japanese Society of Tribologists